Automatic online buffer capacity (alkalinity) measurement of wastewater using an electrochemical cell - Cheng, Liang; Charles, W.; Cord-Ruwisch, R. (Taylor & Francis Ltd., 2016)
© 2016 Taylor & Francis. The use of an automatic online electrochemical cell (EC) for measuring the buffer capacity of wastewater is presented. pH titration curves of different solutions (NaHCO 3 , Na 2 HPO 4 , real municipal wastewater, and anaerobic digester liquid) were obtained by conventional chemical titration and compared to the online EC measurements. The results show that the pH titration curves from the EC were comparable to that of the conventional chemical titration. The results show a linear relationship between the response of the online EC detection system and the titrimetric partial alkalinity and total alkalinity of all tested samples. This suggests that an EC can be used as a simple online titration device for monitoring the buffer capacity of different industrial processes including wastewater treatment and anaerobic digestion processes.